ANTIOXIDANT ACTIVITY OF 96% ETANOL EXTRACT OF KROKOT PLANT (Portulaca oleraceae L.) IN FACE SPRAY PREPARATION BY DPPH METHOD - Dina Pratiwi; Abdul Aziz Setiawan; Dede Anggraeni (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Krokot plants (Portulaca oleracea L.) are weeds that are commonly found in rice fields, plantations, and home yards. Krokot plants have many benefits, including their use as antirheumatic, antibacterial, and antioxidant drugs. The secondary metabolites contained in krokot plants, namely flavonoids, act as the main bioactive compounds. This study aimed to determine the physical properties of face spray preparations and the antioxidant activity of extracts and face spray preparations of 96% ethanol extract of krokot plant (Portulaca oleracea L.) to prevent free radicals. The research method used was Descriptive and inferential analyses were conducted in this study. Krokot plant extract was prepared by maceration using 96% ethanol solvent at a ratio of 1:10 and then used as the active ingredient of formulation (F) at various concentrations of face spray formulations. F1 as negative control, F2 at 0.7%, F3 at 1.4%, and F4 at 2.8%. The results of the physical evaluation of face spray preparations for all formulas met the requirements (organoleptic, pH, homogeneity, dry time test, viscosity, and spray spreadability test). The antioxidant activities of face spray preparations in F1, F2, F3, and F4 had IC50 values of 110.914, 106.581, 85.261, and 64.936 ppm, respectively. The conclusion of this study is that the extract and face spray preparation formula of 96% ethanol extract of krokot plant (Portulaca oleracea L.) have antioxidant activity. Formula 4 showed the best physical properties of face spray preparation. Keywords: Formulation, krokot plant extract, face spray, antioxidant.